Engagement Strategies, Feasibility and Potential Impact of Group CBT for Psychosis Offered Within Assertive Community Treatment - Francoeur, Audrey; Hache-Labelle, Catherine; Samson, Crystal; Vézina, Martin; Lecomte, Tania (Sante mentale au Quebec, 2018)
Objectives The study aims to document the strategies used to facilitate the engagement of participating receiving assertive community treatment (ACT) to a group cognitive-behavioral therapy for psychosis (CBTp) given for the first time in that context, and to describe the feasibility of this intervention with these consumers and the involved clinicians.Methods A group CBTp of 24 sessions has been delivered. Participants were recruited from both teams ACT of Laval, Quebec. Different strategies were elaborated and documented in order to promote participants' engagement to the therapy. Participants had to fill in the following questionnaires: Self-Esteem Rating Scale - Short Form; Brief Symptom Inventory; and Social Provision Scale before and after the therapy.Results The descriptive data show that the strategies from the Positive reinforcement category were the most used, closely followed by Materials and services, and then by the strategies that aim to compensate Memory problems. Participants showed up on average at 76% of the sessions. Four participants on eight had an improvement on their global self-esteem score, 3 improved on social support and 3 improved their global severity index of the BSI symptoms.Conclusion The information gathered could be very important for other ACT teams that wished to carry out a CBTp among the targeted customer base. These consumers could particularly benefit from this group CBTp considering it could diminish social isolation and marginalization often lived by individuals with severe mental illness.